Muscle activation and kinematic differences between breaststroke swimming and technique/drill exercises: a case study of a world champion breaststroker - Olstad, B. H.; Lauer, J.; Haakonsen, D.; Cabri, J.; Kjendlie, P. L. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
Breaststroke swimmers perform technique and drill exercises in their daily training in order to improve their competitive breaststroke swimming. This has previously been looked upon in different kinematic studies, but no study combined this with surface electromyography. One male world champion breaststroker swam regular breaststroke at 60% and 100% of maximal effort and performed one common technique exercise, 2 breaststroke kicks to 1 breaststroke pull at 100% of maximal effort. Biceps femoris, rectus femoris, gastrocnemius medialis and tibialis anterior were analyzed for four different phases of the breaststroke kick using surface electromyography (sEMG). 3D automatic motion tracking was used to identify the four phases of the breaststroke kick. Integrated EMG (iEMG} for the four phases showed that swimming at 60% and 100% had the highest activation in 15 of the 16 conditions (across the 4 phases and the 4 muscles) while the 1st kick in 2 kicks to 1 breaststroke pull showed a peak for gastrocnemius medialis in phase 4. The lowest iEMG activation occurred during 2 kicks to 1 breaststroke pull in 13 conditions and 0 times in swimming at 60% effort. The study showed different muscle activation patterns between regular breaststroke swimming and a common technique/drill exercise.